Profil Kromatografi Senyawa Aktif Antioksidan dan Antibakteri Fraksi N-Heksana Daun Libo (Ficus variegata Blume) - Rolan Rusli; Myra Puspha Hardina; Fairul Muflihah; Agung Rahmadani (Journal of Tropical Pharmacy and Chemistry, 2015)
Research about chromatographic profile of antioxidant and antibacterial compounds in n-hexane fraction of Libo leaves (Ficus variegata Blume.) has been done in order to know the form of chromatographic profile of antioxidant and antibacterial compounds in n-hexane fraction of Libo leaves. Extraction was done by maceration using methanol. Isolation was done by 2 methods, vacuum liquid chromatography (VLC) then followed by conventional column chromatography. Eluent used are n-hexane-ethyl acetate and methanol-chloroform. The results based on conventional column chromatography are as many as 10 fractions. The fractions are being conducted then by a qualitative testing of the antioxidant activity using DPPH method and antibacterial activity test using bioautography TLC method. The results formed as a chromatographic profile of fraction that contain antioxidant and antibacterial activity, which are as many as 5 fractions (NHB1, NHB3, NHB4, NHC1, NHC3) active as an antioxidant and 4 fractions (NHB1, NHC1, NHC2, NHC3) which are active as an antibacterial. The secondary metabolite contents of the fractions are alkaloid, flavonoid and steroid/terpenoid.